SONOGRAPHIC EVALUATION OF UTERINE FIBROID AT DIFFERENT LOCATIONS IN PATIENT WITH IRREGULAR MENSTRUAL CYCLE (The Research of Medical Science Review, 2025)
Background: Uterine fibroids are a significant reason for horribleness in ladies of a  conception age. There are a few factors that are credited to underlie the turn of events and occurrence of these normal tumors. The most probable show of fibroid is by their impact on the lady's period or pelvic strain side effects. For precise analysis various demonstrative markers on Ultrasound are available which expands the viability of Ultrasound to analyze Uterine Fibroid. Objective: To evaluate the different location of uterine Myoma in patients with Upset menstrual period on Ultrasound. Study design: It was a Descriptive and cross-sectional study design. Material and Methods: The descriptive and cross-sectional review was directed from  August to December 2024 at the Hussain Diagnostic center Lahore and Tehsil Head Quarters Hospital Pattoki. The patients in hospital with irregular menstrual cycle will be recruited in the study A sum of ninety-two patients’ information was gathered. Every one of the patients with uterine mayoma because of heavy bleeding, stomach torment, pelvic pain, aggravation in monthly cycle, it was incorporated to go through ultrasound. Patients presented with H/O Cystectomy and H/O sore were barred. Assessment was made on USG machine HD3 Model (2-5 MHz). Results: Around ninety-two cases were numbered in our requests. The cases were kept in age class 15-30 Years (21.7%), 31-45years (66%),45-60 years (12.3%). As location in uterus was recorded, patients presented with sub-serosal myoma 59 (64.1%), 15-20 years patients (1%),31-45 years patients (3%),46-60 years patients (1%), patients presented with Submucosal myoma 36 (39.1%),15-30 years patients (10.3%),31-45 years patients (27.8%),46-60 years patients (2%). Patients presented with Intramural myoma 52 (53.6%),15-30years patients (7.27%),31-45years patients (32%),46-60years patients (9.27%). As per aggravation in reproductive cycle that are connected with fibroid, Polymenorrhagia 64 (69.6%), dysmenorrhea 60 (65.2%), According to the clinical side effects that connected with fibroid, Abdominal agony 92 patients (100%), Pelvic agony 92(100%), Heavy draining 63(68.5%). Conclusion: As per the goal of our study, it has been concluded that uterine myoma effect on feminine period and Ultrasound can more accurately diagnose Uterine myoma due to its sensitivity and best imaging technique. In summary, while the findings from this study generally align with broader trends in the literature, particularly regarding the prevalence of conditions like dysmenorrhea, polymenorrhea, and menorrhagia, the lack of significant associations between these symptoms and certain uterine characteristics (such as the subserosal wall and globular uterine contour) suggests that other factorssuch as hormonal regulation, genetics, or lifestyle may play a more prominent role in these conditions. These results underline the need for further research, particularly studies with larger sample sizes and more detailed clinical histories, to explore the advanced relationships between uterine abnormalities and menstrual symptoms.